Agency and communion: modeling identity-transformation in recovery from substance misuse. (3rd March 2020) - Rowlands, David; Youngs, Donna; Canter, David
ABSTRACT: Background: Research in the field of substance misuse shows that identity change is key to recovery. Theories typically focus on either personal or social factors in this process; however, a framework encompassing agency and communion has proved useful in understanding narratives in similar populations. Objectives: The study proposes that agency and communion provide useful constructs through which to examine substance misuse and recovery. Method: The Life As A Film\(LAAF) and repertory grids were used to explore agency and communion in a sample of 32 participants. Results: Smallest Space Analysis of LAAF content revealed four narrative structures according to elements of agency and communion. Case examples indicated that agency and communion themes related to a recovery identity, and an absence of themes was associated with substance misuse. Repertory grid analysis revealed a pattern of fixed low agency and communion constructs in cases of substance misuse, and a transformed high agency-communion construct system in cases of recovery. Transformation from a low agency and communion substance-using identity toward a high agency and communion recovery identity was illustrated. Conclusions: The exploratory results highlight the centrality of agentic and communal growth in identity-transformative recovery from substance misuse.